2015
DOI: 10.1113/jp270849
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix molecule brevican is an integral component of the machinery mediating fast synaptic transmission at the calyx of Held

Abstract: Key pointsr The proteoglycan brevican is a major component of the extracellular matrix of perineuronal nets and is highly enriched in the perisynaptic space suggesting a role for synaptic transmission.r We have introduced the calyx of Held in the auditory brainstem as a model system to study the impact of brevican on dynamics and reliability of synaptic transmission. r These data show that brevican is an important mediator of fast synaptic transmission at the calyx of Held. AbstractThe extracellular matrix is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 82 publications
6
71
0
Order By: Relevance
“…In recordings from brain slices in which PNNs were degraded by chondroitinase (by breaking down GAGs of chondroitin sulfate proteoglycans), it was found that there was no change in passive membrane properties in these neurons, or in their ability to fire rapid short-duration action potentials, but that there was reduced and delayed spiking (Balmer 2016). Similar results were obtained in brevican knock-out mice (Blosa et al, 2015). Thus, it appears that PNNs increase the excitability of the ensheathed neurons in response to synaptic inputs.…”
Section: Discussionsupporting
confidence: 86%
“…In recordings from brain slices in which PNNs were degraded by chondroitinase (by breaking down GAGs of chondroitin sulfate proteoglycans), it was found that there was no change in passive membrane properties in these neurons, or in their ability to fire rapid short-duration action potentials, but that there was reduced and delayed spiking (Balmer 2016). Similar results were obtained in brevican knock-out mice (Blosa et al, 2015). Thus, it appears that PNNs increase the excitability of the ensheathed neurons in response to synaptic inputs.…”
Section: Discussionsupporting
confidence: 86%
“…However, because most research on the calyx of Held had been performed in mice or rats but not in ITD-using animals like gerbils (47) or guinea pigs (48), one can only speculate how constant synaptic delays are achieved in the subpopulation described above. A recent study even points to the importance of extracellular matrix, which can be found in the auditory brainstem and midbrain, for rapid synaptic release in the MNTB (49,50). In any case, a multicausal explanation seems likely.…”
Section: Discussionmentioning
confidence: 99%
“…The electrophysiological changes were not due to changes in synapse diameter, cell densities or cell death, suggesting that CSPGs, at least the four removed in this study, were required for synaptic maturation in mixed neuronal and astrocyte cultures (Geissler et al, ). Furthermore, brevican is individually required in vivo for maintaining key aspects of synaptic transmission at primary synapses of the auditory circuitry in mice (Table ) (Blosa et al, ).…”
Section: Glycosaminoglycans In Synapse Formation and Functionmentioning
confidence: 99%